The Influence of Communication from the Ombudsman of the Republic of Indonesia Representative of Gorontalo Province on the Mayor's Political Will and Fulfillment of Public Service Standards in Gorontalo City - Azhary Fardiansyah; Syamsu Rizal; Nur Alim Djalil (Universitas Muhammadiyah Palu, 2024)
This research aims to analyze and explain the influence of the communication of the Indonesian Ombudsman Representative of Gorontalo Province on the Political Will of the Mayor of Gorontalo and the fulfillment of public service standards in the City of Gorontalo, as well as to analyze and explain the influence of Political Will on the fulfillment of public service standards. This type of research is quantitative research, data collection techniques are carried out using questionnaires or questionnaires distributed using a goggle form. The data was then analyzed using the Generalized Structured Component Analysis (GSCA) data analysis technique. The results of this research show that Ombudsman communication has a significant influence on the Mayor's Political Will with a value of 0.906806 (significant). This research also shows that Ombudsman communication has a significant influence on the fulfillment of public service standards in Gorontalo City with a value of 0.762909 (significant). Furthermore, this research also shows that the Mayor's Political Will has a significant influence on the fulfillment of public service standards in Gorontalo City with a value of 0.665309 (significant), so this shows that the Ha hypothesis is proven and acceptable.